Return rates from intertidal foraging from Blombos Cave to Pinnacle Point: Understanding early human economies. Issue 92 (March 2016) - De Vynck, Jan C.; Anderson, Robert; Atwater, Chloe; Cowling, Richard M.; Fisher, Erich C.; Marean, Curtis W.; Walker, Robert S.; Hill, Kim
Abstract: The south coast of South Africa provides the earliest evidence for Middle Stone Age (MSA) coastal resource exploitation by early Homo sapiens . In coastal archaeology worldwide, there has been a debate over the general productivity of intertidal foraging, leading to studies that directly measure productivity in some regions, but there have been no such studies in South Africa. Here we present energetic return rate estimates for intertidal foraging along the southern coast of South Africa from Blombos Cave to Pinnacle Point. Foraging experiments were conducted with Khoi-San descendants of the region, and hourly caloric return rates for experienced foragers were measured on 41 days near low tide and through three seasons over two study years. On-site return rates varied as a function of sex, tidal level, marine habitat type and weather conditions. The overall energetic return rate from the entire sample (1492 kcal h −1 ) equals or exceeds intertidal returns reported from other hunter-gatherer studies, as well as measured return rates for activities as diverse as hunting mammals and plant collecting. Returns are projected to be exceptionally high (∼3400 kcal h −1 for men, ∼1900 kcal h −1 for women) under the best combination of conditions. However, because of the monthly tidal cycle, high return foraging is only possible for about 10 days per month and for only 2–3 h on those days. These experiments suggest that while intertidal resources are attractive, women and children could not have subsisted independently, nor met all their protein-lipid needs from marine resources alone, and would have required substantial additional energy and nutrients from plant gathering and/or from males contributing game.